DIFFERENCES BETWEEN GRANDIOSE AND VULNERABLE NARCISSISM: SELF-ESTEEM, EMOTION DYSREGULATION, AND INTERPERSONAL RELATIONSHIP - Fadhila, Audri Shabrina (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2024)
Introduction – Narcissism is most often associated with someone arrogant, domineering, and conceited which is captured in the term grandiose narcissism. However, it is agreed that there are two different dimensions of narcissism which are grandiose narcissism and vulnerable narcissism. Manifestations of the two dimensions are differently affecting one’s self-esteem and interpersonal relationships. Methods – The researcher used several journals and literature discussing grandiose and vulnerable narcissism including assessment, self-esteem, emotion dysregulation, difficulties in interpersonal relationships, and parenting about grandiose and vulnerable narcissism. Results – Narcissism is an effort to protect one’s self-concept which is characterized by an intense need for validation and admiration that pushes them to seek self-enhancements. There are two types of narcissism which are grandiose and vulnerable narcissism. Vulnerable narcissism is associated with lower self-esteem than grandiose narcissism and in turn, has a more positive association with difficulties in regulating negative emotions than grandiose narcissism. Discuss – The assessment of grandiose narcissism is less of a challenge because of the overt presentation of grandiosity. On the other hand, the assessment of vulnerable narcissism is tricky. The entitlement is usually hidden in these individuals with the overt presentation being fearful, cautious, and easily threatened. Conclusion – Vulnerable narcissists tend to develop social avoidance to cope with their vulnerabilities in a relationship, while grandiose narcissist tends to say positive things about themselves. Keywords: grandiose, narcissism, self-esteem, emotion dysregulation, interpersonal relationship.